دور المعرفة الإستراتيجية في تعزيز التعافي الإستراتيجي دراسة تحليلية لآراء عينة من مديري المصارف الخاصة في مدينة أربيل - ولي, إ.د.أحالم إبراهيم; الطائي, إ.د.محمد عبد حسين; محمد, م.م.چيمن بابكر (Sulaimani Journal for Humanities, 2023)
The research aims to determine the relationship and impact of Strategic knowledge in private Banks, represented by its dimensions (The scope of knowledge, the application of knowledge, the effectiveness of knowledge, the relevance of knowledge), in the dimensions of strategic recovery represented by (Retrenchment Strategy, Deprivation Strategy, Strategy of Return). The general framework of the research is the research problem, which was identified by raising several questions about the nature of the relationship and the effect between the independent variable (strategic knowledge) and the dependent variable (strategic recovery). All of them were subjected to multiple tests, and the questionnaire was used as the main tool for obtaining data. The research followed the descriptive analytical approach, as the main and sub-variables were described, as well as the analysis of relationqships and influence between the variables, representing the research community in all the private banks in the city of Erbil, the Kurdistan Region of Iraq. The sample was represented by (24) banks, and the respondents were (89) heads of scientific departments in the universities selected from. The hypotheses were tested through a set of statistical tests using the computer program (SPSS V.23). The research reached a set of conclusions, the most important of which is the existence of positive correlations and strong influences between the main and sub-variables, at the macro and micro levels. The research suggested a set of proposals, including the necessity of harnessing the strong relations between the two variables and directing them towards serving the researched banks.
Keywords: strategic knowledge; strategic recovery; private banks in Erbil city